Application of Network Reduction Technique in Power System - S.Hemalatha, S.Hemalatha; K.Akash, K.Akash; J.Kamlesh, J.Kamlesh; M.Abirami, M.Abirami; S.Pavithra, S.Pavithra; Sainan, Joshna (Journal of Neonatal Surgery, 2025)
Modern electric power system is characterized by the growing size and complexity of the enormous number of generating units, loads and transmission lines that are included in the system. Studies of power system characteristics usually involve the solution of large numbers of equations, both algebraic and differential. This paper focuses on applying Kron's reduction technique in the power system to reduce the original complex power network model into a smaller network. A Java program is written for Kron’s reduction technique for the ease of calculation of reduced network data. The data obtained from the Kron's reduction technique is employed in the reduced network by using ETAP software. The results obtained are validated by conducting load flow analysis. IEEE 5 and IEEE 30 bus system are taken to demonstrate the effectiveness of the proposed method.